Supported heterogeneous catalysts: What controls cobalt nanoparticle dispersion on alumina - Loedolff, M.; Goh, B.; Koutsantonis, G.; Fuller, Rebecca (Royal Society of Chemistry, 2018)
© 2018 The Royal Society of Chemistry and the Centre National de la Recherche Scientifique. We investigate how a number of physical parameters control the rate and pattern of nanoparticle assemblage onto a commercially available alumina surface. 8 nm ?-Co nanoparticles supported on polycrystalline alumina are found to have areas of both good dispersion and areas of aggregation. A similar pattern of dispersion was also observed for larger (~30 nm) polycrystalline ferromagnetic ?-Co nanoparticles. Acid and base treatment of the amphoteric support material prior to the assemblage process is found to have little impact on dispersion of the particles. Using a nonpolar solvent for the assemblage process eliminates the effect of zeta potential and allows for rapid attachment of particles to the support. Performing the assemblage in a polar solvent is found to significantly decrease the rate of the particle attachment to the support. Despite the slower attachment of particles, there is no impact on the nanoparticle distribution pattern. In contrast to the mixed dispersion observed when assembling nanoparticles on an alumina support, ?-Co nanoparticles are found to disperse uniformly across an ordered mesoporous MCM-41 silica support. It seems likely that a specific chemical interaction between the support surface and nanoparticle are dictating the assemblage process.